EMPLOYEE PERFORMANCE VIEWED FROM COMPETENCE, WORK DISCIPLINE AND REWARD (CASE STUDY IN DINAS PENDIDIKAN KOTA SURAKARTA) - Nur Hidayah; Istiatin Istiatin; Fithri Setya Marwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The goal of this study was to assess the impact of work discipline competence and appreciation on employee performance at Dinas Pendidikan Kota Surakarta. The quantitative descriptive research design was adopted in the study. The population consists of all existing employees and up to 178 persons under the aegis of the Dinas Pendidikan Kota Surakarta, with two types of ASN, namely PNS and TKPK. Multiple linear regression analysis, F-test, T-test, and coefficient of determination were employed as data analysis approaches. According to the findings, the variables of competence, work discipline, and reward components all have a substantial impact on employee performance at Dinas Pendidikan Kota Surakarta. The regression computation revealed that the coefficient of determination (R2) was 0.378. This means that competence, work discipline, and rewards may explain 37.8% of the variation in the dependent variable (employee performance), with the remaining 62.2% explained by variables not included in the study's model. Employee performance, competence, work discipline, and rewards